PREPARASI DAN KARAKTERISASI KITIN DARI KULIT UDANG PUTIH (Litophenaeus vannamei) - Mardiyah Kurniasih; Dian Windy Dwiasi (Universitas Jenderal Soedirman, 2007)
Chitin is one of the most abundant natural polysaccharides produced by many living organisms; it is usually found as a component of crustacean shells. In this paper, Chitin have been isolated from white shrimp (Litophenaeus vannamei). The preparation of chitin using chemical products to deproteinize and demineralize the source material. Characterization included determination of water, ash, fat and protein degree; moreover chitin powder characterize with FTIR and XRD spectroscopy. The result showed that process efficiency of chitin from white shrimp (Litophenaeus vannamei) was 20.95%, with degree of water, ash, fat and protein were 5.39, 2.66, 1.54 and 36.16%, respectively.